Nutrient accumulation in cover crops under contrasting water regimes in the Brazilian cerrado - Silva, Alberto do Nascimento (2022)
Brazilian Cerrado has a dry period, and the inclusion of new species for diversification in the production system needs to be drought-tolerant. This work aimed to evaluate biomass and nutrient accumulation in species with potential as cover crops and grain crops under different water levels. Irrigation treatments were obtained through an irrigation bar with sprinklers with increasing water flows to create a continuous gradient. The experimental design randomized complete blocks in split plots with four replications. The main plots were composed of four water regimes (167 mm, 268 mm, 381 mm and 432 mm), and the subplots were formed by the following cover crops: Amaranthus cruenthus, Chenopodium quinoa and Pennisetum glaucum, the latter already used for this purpose. Amaranthus cruenthus and P. glaucum recorded the highest dry biomass (10.16 and 9.75 Mg ha−1, respectively). Dry biomass production and the cellulose contents decreased with the reduction of water availability for all species. A. cruenthus was the species that most accumulated P (37.42 kg ha−1), K (416.92 kg ha−1), Mg (30.88 kg ha−1), S (43.53 kg ha−1), Fe (2.22 kg ha−1), B (0.124 kg ha−1) and Zn (0.240 kg ha−1 ). Amaranthus cruenthus produced the highest yield. Under high and low water availability conditions, A. cruenthus presents potential as a cover crop and grain cash crop, in addition to accumulating more nutrients; P. glaucum has potential as a cover crop and C. quinoa only for grain production.